2020
DOI: 10.1111/ped.14264
|View full text |Cite
|
Sign up to set email alerts
|

Early tonsillectomy for severe immunoglobulin A nephropathy significantly reduces proteinuria

Abstract: Background: Early multiple-drug therapy for severe childhood immunoglobulin A (IgA) nephropathy prevents the progression of nephritis and improves the long-term prognosis. Recent studies have focused on the relationship between the pathophysiology of IgA nephropathy and tonsillar focal infection, and the efficacy of tonsillectomy with methylprednisolone pulse therapy in children has been demonstrated. However, no study has reported on the relationship between the period from diagnosis to tonsillectomy and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Treatment of patients with IgAN has included several approaches that reduce circulating levels of Gd-IgA1. Tonsillectomy has been widely accepted in Japan [ 86 , 87 , 88 , 89 , 90 ]. Gd-IgA1 production by IgA1-secreting cells in tonsils is related to abnormalities in the expression of glycosyltransferase genes associated with core 1 O -glycosylation [ 91 ].…”
Section: Galactose-deficient Iga1 (Hit #1)mentioning
confidence: 99%
“…Treatment of patients with IgAN has included several approaches that reduce circulating levels of Gd-IgA1. Tonsillectomy has been widely accepted in Japan [ 86 , 87 , 88 , 89 , 90 ]. Gd-IgA1 production by IgA1-secreting cells in tonsils is related to abnormalities in the expression of glycosyltransferase genes associated with core 1 O -glycosylation [ 91 ].…”
Section: Galactose-deficient Iga1 (Hit #1)mentioning
confidence: 99%
“…Recent meta-analyses, primarily including studies from Japanese scholars, indicate that about half of the Japanese subjects showed symptom relief after tonsillectomy alone. For the remaining patients, when combined with steroid therapy, there was a trend of decreased glycosylated IgA levels [ 67 69 ]. Notably, the effectiveness of tonsillectomy in treating IgAN differs between Japanese and Caucasian patients.…”
Section: The Gut-kidney Axis In Iganmentioning
confidence: 99%